"Positive" Plasma tCO2 Tests in Racehorses in New York, Maine, and California Result from Day‐to‐Day Instrument Variability. (June 2014) - Foreman, J; Foreman, C
Abstract : Introduction: Many jurisdictions measure plasma tCO2 to determine if racehorses may have been administered exogenous alkalinizers illegally ("milkshakes"). Our hypothesis was that plasma tCO2 test results vary within a racing jurisdiction due to inter‐day instrument variability. Methods: Individual or daily mean plasma tCO2 test results from New York (n = 584) and Maine (n = 443) Standardbreds and California Thoroughbreds (n = 23, 686) were obtained through legal discovery in adjudicated cases where trainers were accused of tampering with horses resulting in tCO2 concentrations ≥37.0 mmol/L. Daily results were grouped by days on which no horse tested ≥37.0 mmol/L (LOW) or days on which at least one horse tested ≥37.0 mmol/L (HIGH). HIGH days were further subsampled by eliminating "positive" test results ≥37.0 mmol/L (MODIFIED HIGH). With P<0.05 considered significant, differences between groups were compared by Student's t test for means and Mann‐Whitney Rank Sum Test for medians. Results: HIGH tCO2 means (32.9 ± 2.6, 35.2 ± 3.4, 32.6 ± 2.7) and medians (32.9, 35.4, 32.6) for all 3 jurisdictions were higher than LOW means (31.7 ± 2.3, 31.9 ± 4.3, 31.5 ± 0.7) and medians (31.8, 32.9, 31.5) (P<0.001). Even when "positive" tests ≥37.0 were eliminated, MODIFIED HIGH means (32.5 ± 2.2, 33.6 ± 2.6, 32.4 ± 2.5) and medians (32.7, 34.2, 32.5) were still higher than LOW (P<0.001). Conclusions: Unless the population tCO2 mean varies significantly daily, it must be concluded that instrument variability resulted in day‐to‐day differences in plasma tCO2 test results. Without appropriate quality control including correction of individual suspect results to a contemporaneous standard curve, horse trainers may be accused unfairly of tampering when day‐to‐day instrument variability contributes to positive plasma tCO2 test results. Ethical Animal Research: This was a retrospective study investigating laboratory results obtained through adjudication of legal cases before various racing commissions.Sources of funding:  none.Competing interests:  none.